Catfish and Water Spinach Cultivation Using Aquaponics as an Effort to Meet Household-Scale Food Needs in Nagori Raya Usang Village - Nursa'adah (Talenta Publisher Universitas Sumatera Utara, 2024)
Nagori Raya Usang Village is one of the Nagori villages in the Dolog Masagal sub-district, Simalungun Regency, North Sumatra Province. Based on the situation analysis, most village residents' livelihoods are artisans and farmers. The production of water spinach and catfish in Dolog Masagal District is still not optimal, so it is necessary to transfer science and technology in terms of cultivating fish and vegetables using an aquaponic system so that people can start businesses to meet their food needs starting from the household scale. The community service activity was carried out in September – October 2022. The implementation of this activity consists of 3 stages: field survey, outreach, and direct practice in making aquaponics with the community. The community has increased their knowledge and ability by 80% through socialization and direct practice of making aquaponics. The results of this aquaponics can be used for household-scale food consumption for vegetable and fish, or as an alternative additional income for the community.